Evaluating Access and Mobility within a New Model of Supported Housing for People with Neurotrauma: A Pilot Study. Issue 1 (7th April 2016) - Callaway, Libby; Tregloan, Kate; Williams, Gavin; Clark, Ross
Abstract : Objectives: (1) Evaluate the features of purpose-built apartment living on access, environmental control, and home and community mobility of people living with neurotrauma and (2) Examine tenant perceptions of those features. Research design: Observational case series pilot study. Setting: Three apartments within a residential development in Melbourne, Australia. Participants: Three males (aged 30–55 years) with traumatic brain and/or spinal cord injury living in the three separate apartments. Method and procedures: Measures: Two-published measures of user experience of built and technology environments, coupled with customised interdisciplinary post-occupancy evaluation (POE) methods and GPS-enabled mobility tracking. Analysis: Measures completed per manual guidelines and data reported descriptively. Customised measured drawings produced to represent tenants' physical access and mobility. GPS community mobility data plotted on Google Earth. Results: Built design features which enabled access and mobility included linear paths of travel, well-located furnishings, and joinery design that allowed approach from either side using a wheelchair. Personal home furnishing choices posed barriers to physical access. Home automation technologies positively influenced participants' sense of control and independence, but posed learning challenges. Close proximity of housing to accessible public transport and services enabled community travel options. Conclusion: Findings from this pilot study indicate the combination of housing location, design and technologies used, together with availability of local community services, provides an acceptable level of environmental control, access, mobility and tenant experience. Further research is required to determine validity of the novel measures used, and deliver rigorous research design to evaluate those features most important in achieving optimal outcomes.